Analisis Sistem Informasi Akuntansi dalam Meningkatkan Pengendalian Internal: Studi Kasus pada Klinik PT. Hurip Putera Husada - Yudistira, Rizky; Astriani, Devi; Puspitasari, Meliana (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Bookkeeping Data Frameworks increase the value of associations with exact, pertinent, and opportune data. So that organization tasks become more successful and productive as well as the organization's interior administration choices. Inside control is required as an authoritative arrangement and technique to safeguard resources from extortion and blunders. The examination object is the PT facility. Hurip Putera Husada, exclusive which works in the field of general wellbeing administrations. The point of the exploration is to examine the bookkeeping data framework in working on the interior control of PT facilities. Hurip Putera Husada. The creator utilizes elucidating investigation with a subjective methodology. Information examination strategy by gathering, depicting, and dissecting information about bookkeeping data frameworks and inward control frameworks in organizations. The consequences of the examination presumed that subsequent to breaking down the bookkeeping data framework at the Hurip Putera Husada center it was sufficient and assumed a powerful and proficient part in working on inner control in the organization. Nonetheless, it is important to focus on clients of the organization's Zahir framework, particularly the principal server at the facility which is in danger in light of the fact that the framework should be associated with the center's web organization (LAN) so representatives can work the Zahir framework at the organization office and can't utilize it outside the organization